Ord, samfunn og ordbok - Gundersen, Dag (LexicoNordica, 1994)
Changes in society are reflected in the vocabulary (examples are given from Norwegian). New meanings, contrasts and patterns emerge and replace older ones. Dictionaries contribute to an extended synonymy. But they have so far been unable to register, and much less explain, the floating mass of nonlexicalized, but often quite difficult compounds that abound in the everyday language of newspapers and magazines. To create "lexicographical portraits" of words one needs a) a very large word base and b) unlimited storage space, both of which point towards the electronic dictionary.